Eksplorasi Konsep Incomprehensibility of God dalam Iman Kristen - Perlius Telaumbanua; Anwar Three Millenium Waruwu; Martina Novalina; Eddy Simanjuntak (Program Pascasarjana UKIM, 2023)
The article delineates the significance of acknowledging God within the context of the Christian faith, focusing on the concept of the Incomprehensibility of God. The theological dualism approach to comprehending God - based on theory and actualization - highlights the challenges in understanding His essence. This research aims to explore this concept from the perspective of the Christian faith, particularly the recognition of God through Jesus Christ. Utilizing a qualitative method, an analysis of biblical texts and relevant theological literature reveals that while God is not entirely comprehensible, His revelations provide pertinent knowledge. The research findings affirm that the concept of the Incomprehensibility of God restricts human comprehension of God; however, recognition through Jesus Christ serves as the key to a deeper understanding. The recognition of God through Jesus Christ necessitates faith and an intimate relationship with Him.Kata Kunci: Pengenalan Allah, Dualisme Teologis, Incomprehensibility of God, Wahyu Khusus, Pemahaman Manusia Tentang Allah